Reações cíclicas de oxidação e redução de materiais a base de Ni para geração de hidrogênio - Corrêa, João Vítor Soares (Universidade Federal de São Carlos, 2017)
Hydrogen (H2) is used in several industrial processes, including ammonia production and petroleum refining. Commercially, most of the H2 produced is from methane steam reforming. Although well established industrially, methane steam reforming requires high energy demand and has problems of catalyst deactivation. As an alternative, this work presents the methane conversion to H2 through chemical looping reactions. This process consists in reacting a metal oxide (MeO) with methane (reducing agent) producing CO and H2 in the gas phase and reduced metal (Me) in the solid phase. Then, regeneration of the Mel is carried out with an oxidizing agent (air, for example), again producing MeO. To make this technology viable, the development of oxygen transporting materials that present high activity, selectivity and stability in the two reaction stages is essential. In this work, Ni/NiO based materials supported on different metal oxides were synthesized. The materials were prepared by wet impregnation and characterized by thermogravimetry, X-ray diffraction, programmed temperature reduction, surface area (BET method), pore volume and transmission electron microscopy. Reactive tests were carried out using methane as reducing agent and oxygen as oxidizing agent. In general, the materials showed activity in both stages of reaction and it was verified that the support exerts influence in the behavior of the formation of the products and the characteristics of Ni/NiO particles.
Keywords: Reforma a vapor; Oxidação; Hidrogênio; Oxidation; Hydrogen; ENGENHARIAS::ENGENHARIA QUIMICA